Compensation and Islamic Corporate Governance as Predictors of Fraud Tendency: The Moderating Role of Religiosity among BMT Employees in Semarang - Rifka Fitriyani Ainurriza; Muchlis Yahya; Joko Prasetiyo (Journal of Business, Social and Technology, 2026)
Background: Fraud exposure can erode the legitimacy and operational resilience of Islamic microfinance institutions. Objective: This study assesses whether compensation and Islamic Corporate Governance (ICG) are related to employees’ fraud tendency and whether religiosity changes these relationships. Methods: A cross-sectional questionnaire survey of 78 employees from BMTs affiliated with PBMTI MPD Semarang City was analysed using partial least squares structural equation modelling in SmartPLS 3.0. Results: Higher compensation and stronger ICG were associated with lower fraud tendency. Religiosity significantly interacted with compensation, but its interaction with ICG was not statistically significant. Conclusion: Fraud-risk management in BMTs should combine fair and transparent remuneration with sharia-oriented governance; individual religiosity may reinforce the compensation-related association.